Characterizing the quantumness of mixed-state ensembles via the coherence of Gram matrix with generalized α-z-relative Rényi entropy. (1st December 2022) - Yuan, Wendao; Wu, Zhaoqi; Fei, Shao-Ming
Abstract: The Gram matrix of an ensemble of pure states can be regarded as a quantum state, and the quantumness of the ensemble can be quantified by the coherence of the Gram matrix. By using the affinity between mixed states, the concept of Gram matrix of pure-state ensembles can be extended to the one of mixed-state ensembles. By utilizing the generalized α - z -relative Rényi entropy of coherence of Gram matrices, we present a new quantifier of quantumness of mixed-sate ensembles and further reveal its peculiar properties. To illustrate our quantumness of mixed-sate ensembles, we also calculate the quantumness for some detailed mixed-sate ensembles by deriving their analytical formulae.